(untitled) (World Marxist Review, 2026)
This paper highlights that Marx’s algebraic, infinitesimal-free and limit-free method of differentiation also involves an algorithm for the recursive determination of higher-order derivatives based on the Taylor– Lagrange Theorem. This fact is relevant to the ongoing debates both on the evaluation of Marx’s Mathematical Manuscripts and on alternative ways of approaching and teaching the history and subject matter of calculus